Fifty key thinkers in psychology - Sheehy, Noel, 1955- (Routledge, 2004)
This book focuses on fifty major influential figures on psychology, ranging from the earliest days of the discipline 200 years ago to the present day. It provides concise biographical information on each thinker, and then proceeds to examine their contributions to the evolution of psychology as a discipline, and provides a commentary on their ideas and works. Accessibly written and with guides to further reading, Fifty Key Thinkers in Psychology is an invaluable resource for the student, practitioner and general reader alike.--Anotace od vydavatele
Terminologický slovník
Keywords: psychologie; psychologové; dějiny psychologie; psychology; psychologists; history of psychology; biografické slovníky; biographical dictionaries